PP071 - Morita, Yoshihiro; Hata, Kenji; Nakanishi, Masako; Yonekawa, Atsuko; Iwagami, Takaki; Iwai, Soichi; Omata, Tetsuji; Kobayashi, Kazuyo; Morita, Nobuo; Nishimura, Riko; Yura, Yoshiaki; Yoneda, Toshiyuki (Oral oncology, 2013)
Purpose Lymph node metastasis is a key prognostic determinant in cancer patients. To understand the molecular basis underlying lymph node metastasis, we studied the SAS oral squamous cancer cells which metastasized to the regional lymph nodes following tongue inoculation. Material and methods In our previous study, highly metastatic SAS cells (SAS-LM8) were established by repeated in vivo inoculation and FACS selection. Lymphangiogenesis was determined by immunohistochemistry using anti-LYVE1 antibody, well-established marker for lymphatic vessels. Results SAS-LM8 tumors showed increased lymphangiogenesis and elevated expression of VEGF-C, a potent stimulator of lymphangiogenesis, compared to parental SAS tumors. A metastasis real-time PCR array demonstrated that 6 genes including fibronectin1 (FN1) were at least 4-fold upregulated in SAS-LM8 compared with SAS. FN1 is one of the epithelial mesenchymal transition (EMT) makers. Further analyses revealed that this cell line exhibited phenotypic and molecular alterations consistent with EMT. Importantly, knockdown of FN1 using shRNA decreased VEGF-C expression and lymphangiogenesis. Consistent with these results, immunohistochemical analysis of human oral cancer tissues revealed that the expression of FN1 and VEGF-C significantly correlates with the lymph node metastasis. Conclusions SAS-LM8 was subject to EMT and mediated by increased FN1. Our results suggest that VEGF-C expression under the control of FN1 plays a critical role in lymph node metastases and that suppression of FN1 and VEGF-C may be a feasible therapeutic approach for lymph node metastasis.